Oil quality and sugar content of peanuts (Arachis hypogaea) grown in Argentina : their relationship with climatic variables and seed yield - Casini, Cristiano; Dardanelli, Julio Luis; Martinez, Maria Jose; Nassetta, Mirtha; Borgogno, Carmen S.; Balzarini, Mónica Graciela (ACS Publications, 2017)
The ratio of oleic to linoleic acids (O/L) and the tocopherol content are important features in determining peanut (Arachis hypogaea) seed shelf life. Soluble carbohydrates are known to be important precursors in roasted peanut flavor. The chemical qualities of Argentine grain are different from those of other countries, but no previous studies that associate grain quality and environmental parameters have been performed. Relationships were determined between O/L, tocopherol and sugar contents, and variations in temperature and rainfall during the grain filling period of Florman INTA peanuts. Dry seed yield was used as another explanatory variable. Multiple regression procedure gave mean temperature (positive coefficient) and total precipitation (negative coefficient) as the explanatory variables for variations in O/L. Total precipitation and dry seed yield (both negative coefficients) were found to be predictor variables for tocopherol and sugar contents. Total precipitation was an explanatory variable included in all of the linear regression models obtained in this study.